Behavioral Aspects: Search Engine optimization Strategy focusing for new entrants - et. al., S. Namdhini, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The main objective of this research is to identify the problems faced in marketing and sales of industrial flooring products in speciality flooring chemicals industries. The major problems that was noticed here was that industries that use flooring stick to existing supplier or purchasing from supplier who are already in market. Understanding this problem for new entrants, a strategy was developed for marketing to overcome the obstacle faced by new industrial flooring companies. To indentify further details on this, a survey was conducted mostly among industries and few restaurants to come to a conclusion on the decision factor for strategy and analysed responses highlighted the reason for not using and also why do they stick to existing supplier if they are using industrial flooring. The suggestion that has been made in this report is use of an effective search engine optimization strategy (SEO) will increase the web traffic to 50% of those who use the internet these days for such purpose. Once this done next is to implement social sales that is educate, social network and engage which can be used to make them aware about the necessity of industrial flooring which increases sales by almost 40%. All these plans may be different in names by they come under the concept of Account Based Marketing (ABMs) which is developing and effective marketing strategy that has constructive impact on company’s revenue.